Methodological guidelines for laboratory works in the "System software" academic discipline - Panchenko, Volodymyr Ivanovych; Glavchev, Maksym Igorovych; Heiko, Hennadii Viktorovych (Національний технічний університет "Харківський політехнічний інститут", 2026)
These methodological guidlines review basic theoretical information regarding the development of system software for the Linux operating system (OS). Each topic is illustrated with program texts. For Linux OS, the C programming language is used (program texts for the examples in topics 1 –8 were developed and tested in Ubuntu 22.04.4 LTS using the cc compiler). The main mechanisms for managing processes, utilizing synchronization tools, and performing data exchange are considered. The system mechanisms discussed in these topics allow students to obtain practical skills in system programming for the Linux OS and serve as a practical reinforcement of the material taught in the "System Software" discipline. Review questions are provided after each topic to reinforce the theoretical material. A general list of recommended literature is provided for the discussed topics. Additionally, for studying materials and developing programs, the resource https://manpages.ubuntu.com/ (specifically the "System calls" help sections) may be required. The topics considered are used in the laboratory practicum for the "System Software" discipline. A number of individual practical tasks have been formed for each topic to reinforce the material. Report formatting is performed according to generally accepted requirements.
Keywords: methodological guidelines; laboratory works; system software; computer engineering; Windows operating system; C++ programming language